The tourism function of rural areas in Pomerania province: diversity and change - Durydiwka, Małgorzata (Turyzm/Tourism, 2015)
The aim of this paper is to present the spatial diversity of the tourism function in the rural areas of Pomerania province and the changes which occurred in 1995-2013. The tourism function has been determined by means of two characteristics: the number of tourists using accommodation and the number of businesses registered in the REGON system in sections H or I. To quantify the tourism function a synthetic measure has been used according to a procedure by ZIOŁO (1973). Based on this, five levels of the development of the tourism function have been determined. The quantitative and spatial changes occurring in the development of the tourism function in rural areas have then been analyzed. Particular emphasis has been placed on the so-called tourism communes, i.e. those where the tourism function is at least at a ‘moderate’ level of development. For these communes, nine functional types have been determined, based on two characteristics (average duration of stay and share of year-round accommodation), changes which occurred in this respect in 1995-2013 have also been determined.